Computer Vision in Control Systems-3 Aerial and Satellite Image Processing - Favorskaya, Margarita N.; Jain, Lakhmi C.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
The research book is a continuation of the authors' previous works, which are focused on recent advances in computer vision methodologies and technical solutions using conventional and intelligent paradigms. The book gathers selected contributions addressing aerial and satellite image processing and related fields. Topics covered include novel tensor and wave models, a new comparative morphology scheme, warping compensation in video stabilization, image deblurring based on physical processes of blur impacts, and a rapid and robust core structural verification algorithm for feature extraction in images and videos, among others. All chapters focus on practical implementations.   Given the tremendous interest among researchers in the development and applications of computer vision paradigms in the field of business, engineering, medicine, security and aviation, this book offers a timely guide.
Theoretical and Practical Solutions in Remote Sensing -- Multidimensional Image Models and Processing -- Vision-Based Change Detection Using Comparative Morphology -- Methods of Filtering and Texture Segmentation of Multicomponent Images -- Extraction and Selection of Objects in Digital Images by the Use of Straight Edges Segments -- Automated Decision Making in Road Traffic Monitoring by On-Board Unmanned Aerial Vehicle System -- Warping Techniques in Video Stabilization -- Image Deblurring Based on Physical Processes of Blur Impacts -- Core Algorithm for Structural Verification of Keypoint Matches -- Strip-Invariants of Double-Sided Matrix Transformation of Images -- The Fibonacci Numeral System for Computer Vision.
Keywords: Computational intelligence; Artificial intelligence; Control engineering; Computational Intelligence; Artificial Intelligence; Control and Systems Theory